Red or blue, I like you! - Albee, Sarah; Brannon, Tom (Somerville, Mass. : Candlewick Press, 2008)
Elmo and his new friend Angela learn that even though they have different color fur they like the same thing.
"123 Sesame Street."
2.4
K-3
K-3
Keywords: Elmo (Fictitious character : Henson) -- Juvenile fiction; Toleration -- Juvenile fiction; Prejudices -- Juvenile fiction; Muppets (Fictitious characters) -- Juvenile fiction; Oversize books -- Specimens; Elmo (Fictitious character : Henson) -- Fiction; Toleration -- Fiction; Prejudices -- Fiction; Muppets (Fictitious characters) -- Fiction; Oversize books; Elmo (Fictional character : Henson) -- Fiction; Toleration -- Fiction; Prejudices -- Fiction; Muppets (Fictional characters) -- Fiction; Big books